2022
DOI: 10.3390/jcm11154334
|View full text |Cite
|
Sign up to set email alerts
|

Episiotomy for Medical Indications during Vaginal Birth—Retrospective Analysis of Risk Factors Determining the Performance of This Procedure

Abstract: The WHO (World Health Organization) recommends that the percentage of perineal incisions should not exceed 10%, indicating that this is a good goal to achieve, despite the fact that it is still a frequently used medical intervention in Poland. The risk factors for perineal incision that have been analyzed so far in the literature allow, among others, to limit the frequency of performing this procedure. Are they still valid? Have there been new risk factors that we should take into account? We have conducted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
1
0
1
Order By: Relevance
“…On the other hand, the mean pain score at one hour after the episiotomy repair in the study group was (3.00 ±1.32) as compared to (5.40± 0.98) in the control group with statistically significant differences among the both group at (p ≤ 0.05). Figure (1) shows the pain score during the episiotomy repair, it was found that, 48% of women in the study group had mild pain intensity as compared to 14% in the control group. While, 42% of women in the study group had moderate pain intensity as compared to 72% in the control group.…”
Section: Resultsmentioning
confidence: 92%
“…On the other hand, the mean pain score at one hour after the episiotomy repair in the study group was (3.00 ±1.32) as compared to (5.40± 0.98) in the control group with statistically significant differences among the both group at (p ≤ 0.05). Figure (1) shows the pain score during the episiotomy repair, it was found that, 48% of women in the study group had mild pain intensity as compared to 14% in the control group. While, 42% of women in the study group had moderate pain intensity as compared to 72% in the control group.…”
Section: Resultsmentioning
confidence: 92%
“…Незважаючи на існування загальноприйнятих стратегій лікування епізіотомної рани, що охоплюють фармакологічні та немедикаментозні підходи, удосконалення терапевтичних та діагностичних методів залишається критичною проблемою. Останніми роками розуміння фізіологічного перебігу загоєння епізіотомної рани зазнало значного розвитку, виявивши складний взаємозв'язок між цією процедурою, маркерами запалення, емоційним стресом і болем [2].…”
unclassified